Pain, discomfort and oral health-related quality of life in clear aligner therapy: a contemporary narrative review - Perski, Karol; Zarzycka, Marta; Lorek, Julia; Chrabąszcz, Joanna; Kurek, Maria Michalina; Gadzalski, Krzysztof; Grzywna, Wojciech; Baltyzar, Konstancja Anna; Polit-Różycka, Oliwia Kinga (Quality in Sport, 2026)
Background Clear aligner therapy (CAT) has become a popular alternative to fixed orthodontic appliances due to its aesthetics, comfort, and convenience. Increasing attention in orthodontics is focused on patient-reported outcomes such as pain, discomfort, and oral health-related quality of life (OHRQoL). Aim This narrative review aimed to evaluate evidence regarding pain, discomfort, and OHRQoL in patients treated with clear aligners. Material and methods A literature search was conducted in PubMed, Google Scholar, Scopus, and Web of Science. Studies assessing patient-reported outcomes related to pain, discomfort, psychological factors, and OHRQoL in clear aligner patients were included. Prospective and retrospective studies, as well as randomized controlled trials, were analyzed qualitatively. Due to heterogeneity in study design and outcome assessment, no meta-analysis was performed. Results The reviewed studies indicate that clear aligners are associated with lower pain intensity, reduced discomfort, and higher patient satisfaction compared with fixed appliances. Pain and discomfort were greatest at the beginning of treatment and decreased over time. Clear aligners also improved aesthetics, reduced psychological burden, enhanced patient acceptance, and resulted in more favorable OHRQoL outcomes. Temporary speech and eating difficulties were reported but were generally mild and transient. Interpretation of the evidence is limited by variability in study designs and assessment methods. Conclusions Clear aligner therapy is a patient-centered orthodontic approach associated with improved comfort and favorable patient-reported outcomes while maintaining functional effectiveness. Further high-quality, standardized, and long-term studies are needed to strengthen the evidence and better assess the broader impact of CAT on patient-centered outcomes.